Examining Linkage Between Transactional Leadership, Organizational Culture, Commitment and Compensation on Work Satisfaction and Performance - Nurlina, N. (Manunggal Halim Jaya, 2022)
The purpose of this study was to analyze the effect of transactional leadership, organizational culture, commitment, and compensation on job satisfaction. The research was conducted at the Agricultural Quarantine Center for the South Sulawesi Region with a population of 193 respondents. Data from the questionnaire were analyzed using the Structural Equation Model using the help of AMOS 18. The results found that transactional leadership directly had a positive and significant effect on employee job satisfaction. Organizational culture has a negative and significant effect on employee job satisfaction. organizational commitment has a significant effect on employee job satisfaction. Compensation has a significant effect on employee job satisfaction. Transactional leadership directly has a significant effect on employee performance. Organizational culture has insignificant effect on employee performance. Organizational commitment has significant effect on employee performance. Compensation has significant effect on employee performance. Job satisfaction has significant impacts employee performance. Indirectly, transactional leadership through job satisfaction positively and significantly affects employee performance. Indirectly, organizational culture through job satisfaction has a negative and insignificant effect on employee performance. Indirectly, organizational commitment through job satisfaction positively and significantly affects employee performance. Indirectly, compensation through job satisfaction has a positive and significant effect on employee performance.